2020
DOI: 10.1186/s12904-020-00673-3
|View full text |Cite
|
Sign up to set email alerts
|

Is early integration of palliative home care in oncology treatment feasible and acceptable for advanced cancer patients and their health care providers? A phase 2 mixed-methods study

Abstract: Background To support the early integration of palliative home care (PHC) in cancer treatment, we developed the EPHECT intervention and pilot tested it with 30 advanced cancer patients in Belgium using a pre post design with no control group. We aim to determine the feasibility, acceptability and perceived effectiveness of the EPHECT intervention. Methods Interviews with patients (n = 16 of which 11 dyadic with family caregivers), oncologists and GPs (n = 11) and a focus group with the PHC team. We further an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 43 publications
1
3
0
Order By: Relevance
“…Consistent with the exploratory study aims, the feasibility endpoint was determined by the authors primarily balancing pragmatic considerations around the available study timeframe. It was consistent with other phase II studies of this nature (34) and also considered the minimum sample required to determine a preliminary estimate of effect size for secondary patient-reported outcomes which would be the subject of a future phase III definitive trial.…”
Section: Primary Endpointsupporting
confidence: 56%
“…Consistent with the exploratory study aims, the feasibility endpoint was determined by the authors primarily balancing pragmatic considerations around the available study timeframe. It was consistent with other phase II studies of this nature (34) and also considered the minimum sample required to determine a preliminary estimate of effect size for secondary patient-reported outcomes which would be the subject of a future phase III definitive trial.…”
Section: Primary Endpointsupporting
confidence: 56%
“…[44][45][46][47] To tackle this problem, co-rounding could be adapted with integration of oncology with community-based palliative care. 48 Such a model extending into the community could be made feasible with rise of tele-collaboration use cases that allow "virtual co-rounding" between off-site oncologist and on-site community palliative care team, all within a patient's home. 49 Additionally, such consults can help prevent the sense of abandonment and lack of continuity often reported at end-of-life.…”
Section: Discussionmentioning
confidence: 99%
“…To ensure patient involvement in decisions about their health and wishes for the future, adequate information about treatment options and symptom relief is deemed an essential prerequisite for patients in need of palliative care [ 6 ]. Dhollander et al [ 7 ] found that patients experienced benefits from discussions with nurses concerning their preferences for the future. Nevertheless, their preferences regarding how they wished to be involved in the decision-making processes were not explored, nor was the significance of reflecting on their wishes clarified.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, their preferences regarding how they wished to be involved in the decision-making processes were not explored, nor was the significance of reflecting on their wishes clarified. Dhollander et al [ 7 ] also emphasized the importance of advance care planning (ACP), which is the creation of a plan for treatment intensity in the event of a worsening health condition based on the patient’s values, goals, and preferences [ 5 , 8 ]. Using such approach, Dhollander et al [ 7 ] underline the importance of an early integration of palliative care in the patient’s treatment from a home care perspective.…”
Section: Introductionmentioning
confidence: 99%